Childhood Memory, Family Dynamics, and Rumination: A Systematic Review in a Psychological Perspective - Marita, Prily Carla; Hendriani, Wiwin (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The family is included in the smallest and closest circle to an individual. Family becomes the first environment to interact with an individual. Not all children go through a childhood full of laughter; some experience challenging childhoods, often referred to in psychology as adverse childhood experiences. This study aimed to analyze the influence of childhood memories and family dynamics on rumination tendencies through a systematic review, in order to understand the underlying psychological factors and the role of emotional memory in repetitive thinking among individuals. This study employed a systematic literature review method, with data collected from four journal portals: one national journal and three international journals. The national journal portal used was Garuda, with the search keywords "ruminasi" and "rumination." International journal portals included SAGE, Emerald Insight, and JSTOR, with search keywords "impact AND rumination family OR childhood matters OR experience." The study results indicated that rumination impacts various aspects, including interpersonal relationships, academic achievement, behavior, emotions, and psychological disorders. Rumination influences interpersonal relationships, especially in peer relations, and negatively impacts academic performance. The implications of this study highlight the need for psychological interventions focused on rumination management, particularly related to family experiences. Keluarga termasuk dalam lingkaran terkecil dan terdekat bagi individu. Keluarga menjadi lingkungan pertama yang berinteraksi dengan individu. Tidak semua anak melewati masa kecil yang penuh tawa. Ada pula anak-anak yang mengalami pengalaman masa kecil yang berat atau dalam psikologi biasa disebut sebagai adverse childhood experience. Penelitian ini bertujuan untuk menganalisis pengaruh memori masa kecil dan dinamika keluarga terhadap kecenderungan rumination melalui tinjauan sistematis, guna memahami faktor psikologis yang mendasari serta peran memori emosional dalam proses berpikir berulang di kalangan individu. Penelitian ini menggunakan metode systematic literature review. Data dikumpulkan dari 4 portal jurnal. 1 jurnal nasional dan 3 jurnal internasional. Portal jurnal nasional yang digunakan adalah Garuda dengan menggunakan kata kunci pencarian “ruminasi” dan “rumination”. Portal jurnal internasional yang digunakan adalah SAGE, Emerald Insight, dan JSTOR dengan kata kunci pencarian “impact AND rumination family OR childhood matters OR experience”. Hasil penelitian menunjukkan bahwa ruminasi berdampak pada berbagai aspek, termasuk hubungan interpersonal, capaian akademik, perilaku, emosi, dan gangguan psikologis. Ruminasi mempengaruhi hubungan interpersonal, khususnya dalam relasi teman sebaya, serta berdampak negatif pada prestasi akademik. Implikasi penelitian ini menunjukkan perlunya pengembangan intervensi psikologis yang fokus pada manajemen ruminasi, terutama yang berhubungan dengan pengalaman keluarga.